Struktur Nalar Arab-Islam menurut ‘Âbid Al-Jâbirî - Faishol, M. (Religió: Jurnal Studi Agama-agama, 2013)
The project of ‘Âbid Al-Jâbirî’s thoughts has become epistemological critic to traditional frame of Islam-Arab knowledge through analyzing socio-political background on the logic of Arab formulation. According to Al-Jâbirî, the logic of Arabic thought could be devised into three methods: bayâni, ‘irfâni and burhâni. Therefore, the structure of Islam-Arab culture has occurred based on: (1) authoritative texts—because the logic of Arab is exceedingly based on religious texts, (2) authoritative salaf, that is, focused on ‘ulama’s considerations, and (3) authoritative permissivism along with anti-causality (sult}ah at-tajwîz al-lâsababiyyah). Hence, Arabic culture becomes unproductive, poor of concept and theory. As a solution, Al-Jâbirî invites to contextualize the spirit of critic such as rational-empiricism of Ibn Hazm and al-Shâtibî on fiqh, Ibn Rushd on philosophy, Ibn Khaldûn on sociology, etc. This article will probe specifically about ‘Âbid Al-Jâbirî’s reform thought. Al-Jâbirî’s thinking distinctiveness lies in the epistemological critique conducted on the science that develops in the Arab-Islamic civilization. The epistemological critique becomes a realm of science that not much attention, especially by Muslim thinkers. Al-Jâbirî’s epistemological critique offers to the Muslim world an attempt to reconstruct the building of reason-epistemic knowledge to keep pace and change its Islamic world towards the progress of civilization.